LITERATURE STUDY OF THE RELATIONSHIP OF DINING AND BREAKFAST PATTERNS WITH LEARNING ACHIEVEMENT IN BASIC SCHOOL CHILDREN - Elisa Christy Simanjuntak; Tariana Ginting; Perry Boy Siahaan; Buenita Buenita (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2020)
School children are the nation's next generation. Therefore, it is necessary to improve human resources from an early age. Providing good nutrition, will affect the growth and development of a child. The purpose of this study was to determine the relationship between eating and breakfast patterns and learning achievement of elementary school children. The type of research used is quantitative research with a literature study design. The literature used is literature published from 2013 to 2020. The results of data analysis show that there is a relationship between eating and breakfast patterns and learning achievement of elementary school children. The results of data analysis showed that there were 3 research locations, namely in Java 60% (6 articles), Sulawesi 30% (3 articles), Kalimantan 10% (1 article). Using correlation research 50%, analytic survey research 20%, and 30% other research. Data analysis was made in univariate and bivariate ways. The variables used in each study were diet, breakfast, and learning achievement. From this research, it can be concluded that there is a relationship between eating and breakfast patterns and learning achievement of elementary school children. So further research is expected to develop other factors that can affect student achievement.